"Many a good, old honest woman hath been condemned innocently": Cavendish and Glanvill on witchcraft - Vuletić Miloš (Belgrade Philosophical Annual, 2024)
Margaret Cavendish and Joseph Glanvill disagreed over the reality of witchcraft. In her assessment of the exchange between the two, Jacqueline Broad finds that Cavendish was the "voice of scientific reason", not only because of her disbelief in witchcraft but also because her arguments show that Glanvill violated scientific principles to which he subscribed. This paper reassesses the disagreement and comes up with two conclusions. First, Glanvill's position is not as internally unstable as Broad's analysis suggests. Second, Cavendish can indeed be viewed as a voice of scientific reason, but in a different sense: she expresses the spirit of the seventeenthcentury natural philosophy insofar as she accepts precisely those elements of magical and occult traditions that did end up incorporated into science, and rejects those that were cast aside, witchcraft included.